Outcome of mitral valve repair in a patient with systemic lupus erythematosus - Roshanali, Farideh (BMJ Case Rep, 2012)
We present a 17-year-old woman with a 5-year history of systemic lupus erythematosus (SLE). The patient referred to us with the rheumatic involvement of the mitral valve and was treated with mitral valve repair by ring annuloplasty and anterior leaflet augmentation with autologous pericardium. Follow-up, however, disclosed precocious calcification of the valve, necessitating mitral valve replacement.